Polyester resin particles and cosmetic

By integrating a furan structure into the polyester resin particles, the challenge of achieving high refractive index and biodegradability is addressed, resulting in particles suitable for diverse applications.

JP2025059851APending Publication Date: 2025-04-10SOKEN CHEM & ENG CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023170200
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-29
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

Existing polyester resin particles face a challenge in achieving a high refractive index while maintaining biodegradability, as the use of aromatic raw materials can reduce biodegradability.

Method used

Incorporating a furan structure into the polyester resin particles, which allows for a high refractive index and high biodegradability, by using furan-derived monomers in the polymerization process.

Benefits of technology

The resulting polyester resin particles exhibit both high refractive index and high biodegradability, making them suitable for a wide range of applications, including cosmetics and optical uses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025059851000001_ABST
    Figure 2025059851000001_ABST
Patent Text Reader

Abstract

To provide polyester resin particles having a high refractive index and high biodegradability.SOLUTION: According to the present invention, polyester resin particles comprising a polyester resin including a furan structure are provided.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to polyester resin particles. [Background technology]

[0002] In recent years, there has been an increasing demand for environmentally friendly and sustainable products. Polyester materials have attracted attention as one of the materials that can meet these demands, and polyester resin particles are used in a wide range of applications, such as cosmetics, optical applications, and medical applications.

[0003] Patent Document 1 discloses polyester particles which are obtained by condensation of a polycarboxylic acid component, either one or both of which contains 2.0 mol % or more of an unsaturated polycarboxylic acid or an unsaturated polyhydric alcohol, and a polyhydric alcohol component, and which mainly contain a polyester resin containing ionic groups in the range of 20 to 500 eq. / ton, have a volume average particle diameter D of 0.1 to 100 μm, particles with particle diameters in the range of 0.5D to 2.0D account for 80% by weight or more of the total, have a coefficient of variation of 30% or less, and have an average sphericity (minor axis / major axis) of 0.8 or more.

[0004] Furthermore, Patent Document 2 discloses a method for producing polyester particles, which comprises adding an electrolyte to an aqueous microdispersion of an ionic group-containing polyester having an average particle size of 0.1 μm or more under conditions in which the ionic group-containing polyester is plasticized, thereby leading the microdispersed particles to a slow aggregation region and causing particle growth. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 6-263882 [Patent Document 2] Japanese Patent Application Publication No. 6-145367 Summary of the Invention [Problem to be solved by the invention]

[0006] Resin particles are required to have a high refractive index depending on the form of use. One method for increasing the refractive index of polyester resin particles is, for example, to use aromatic raw materials. However, the use of aromatic raw materials may result in a decrease in biodegradability.

[0007] The present invention has been made in view of the above circumstances, and provides polyester resin particles which have a high refractive index and are highly biodegradable. [Means for solving the problem]

[0008] According to the present invention, polyester resin particles having a high refractive index and high biodegradability are provided.

[0009] As a result of extensive investigations, the present inventors have found that by incorporating a furan structure into a polyester resin, polyester resin particles having a high refractive index and high biodegradability can be obtained, leading to the completion of the present invention.

[0010] Various embodiments of the present invention will be described below. The embodiments described below can be combined with each other. [1] Polyester resin particles comprising a polyester resin containing a furan structure. [2] The polyester resin particles according to [1], wherein the polyester resin has a hydrophilic group. [3] The polyester resin particles according to [1] or [2], wherein the polyester resin contains a structure derived from a polyvalent carboxylic acid and a structure derived from a polyhydric alcohol, and the structure derived from the polyvalent carboxylic acid contains the furan structure. [4] The polyester resin particles according to [3], wherein the structure derived from the polyhydric alcohol includes a structure derived from a linear aliphatic diol having 2 to 4 carbon atoms. [5] The polyester resin particles according to any one of [1] to [3], having a sphericity of 0.90 to 1.00. [6] The polyester resin particles according to any one of [1] to [3], having an average particle size of 1 to 30 μm. [7] A cosmetic comprising the polyester resin particles according to any one of [1] to [6]. Effect of the Invention

[0011] According to the polyester resin of the present invention, it is possible to provide resin particles having a high refractive index and high biodegradability. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is an image of the polyester resin particles (1) according to Example 1 taken by a scanning electron microscope. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The present invention will be described in detail below by illustrating the embodiments of the present invention. The present invention is not limited by these descriptions. The features of the embodiments of the present invention described below can be combined with each other. In addition, each feature can be an invention independently.

[0014] 1. Polyester resin particles The polyester resin particles according to the present invention include a polyester resin containing a furan structure. The polyester resin particles according to one embodiment of the present invention may contain 50 to 100% by mass of polyester resin when the polyester resin particles are taken as 100% by mass. The content of the polyester resin in the polyester resin particles may be, for example, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, or 100% by mass, and may be within a range between any two of the numerical values ​​exemplified here. The polyester resin particles according to one embodiment of the present invention may contain 50 to 100% by mass of polyester resin containing a furan structure when the polyester resin particles are taken as 100% by mass. The content of the polyester resin containing a furan structure in the polyester resin particles may be, for example, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, or 100% by mass, and may be within a range between any two of the numerical values ​​exemplified here.

[0015] 1.1 Structural units and their contents in polyester resin In the present invention, the polyester resin means a polymer having an ester bond in the main chain, specifically, a polymer having a plurality of structures in which polyvalent carboxylic acids and polyhydric alcohols are ester-bonded in the main chain. The polyester resin according to one embodiment of the present invention can be obtained by polycondensation of raw material monomers including polyvalent carboxylic acids and polyhydric alcohols. The polyester resin according to one embodiment of the present invention has at least a structure derived from polyvalent carboxylic acids and a structure (structural unit) derived from polyhydric alcohol. The polyester resin according to one embodiment of the present invention preferably has at least a structure derived from dicarboxylic acids and a structure (structural unit) derived from diol. The polyester resin according to the present invention contains a furan structure. In the present invention, containing a furan structure means having a structure derived from a monomer having a furan structure. In the polyester resin according to one embodiment of the present invention, at least one of the structures derived from polyvalent carboxylic acids and the structures derived from polyhydric alcohols may contain a furan structure, i.e., the polyester resin may contain at least one of a structural unit derived from a polyvalent carboxylic acid containing a furan structure and a structural unit derived from a polyhydric alcohol having a furan structure. In the polyester resin according to one embodiment of the present invention, the structure derived from a polyvalent carboxylic acid preferably contains a furan structure, and it is preferable that the polyester resin has a structure derived from a polyvalent carboxylic acid having a furan structure.

[0016] <Polycarboxylic acids> The polyvalent carboxylic acids include carboxylic acids, carboxylic acid salts, carboxylic acid anhydrides, carboxylic acid halides, carboxylic acid esters, and the like. Polycarboxylic acids include: Aliphatic dicarboxylic acids such as malonic acid, dimethylmalonic acid, succinic acid, glutaric acid, adipic acid, trimethyladipic acid, pimelic acid, 2,2-dimethylglutaric acid, azelaic acid, sebacic acid, fumaric acid, maleic acid, itaconic acid, thiodipropionic acid, diglycolic acid, or these carboxylic acids; Aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, benzylmalonic acid, diphenic acid, 4,4'-oxydibenzoic acid, naphthalenedicarboxylic acid, or these carboxylic acids; Alicyclic dicarboxylic acids such as 1,3-cyclopentanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid, 1,3-cyclopentanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 2,5-norbornanedicarboxylic acid, adamantanedicarboxylic acid, or these carboxylic acids; dicarboxylic acids having a furan structure such as 2,3-furandicarboxylic acid, 2,3-dimethyl furandicarboxylate, 2,3-dipropyl furandicarboxylate, 2,4-furandicarboxylic acid, 2,4-dimethyl furandicarboxylate, 2,4-dipropyl furandicarboxylate, 2,5-furandicarboxylic acid, 2,5-dimethyl furandicarboxylate, 2,5-dipropyl furandicarboxylate, 2,5-diphenyl furandicarboxylate, 3,4-furandicarboxylic acid, 3,4-dimethyl furandicarboxylate, 3,4-dipropyl furandicarboxylate, 3,4-diphenyl-2,5-furandicarboxylic acid, 3,4-diphenyl-2,5-dimethyl furandicarboxylate, 3,4-diphenyl-2,5-dipropyl furandicarboxylate, or these carboxylic acids; These may be used alone or in combination of two or more. The polycarboxylic acids may also include hydrophilic group-containing polycarboxylic acids, as described below. The hydrophilic group-containing polycarboxylic acids will be described later.

[0017] The type of polybasic carboxylic acid used can be selected according to the properties required for the polyester resin particles. For example, when biodegradability and a high refractive index are required for the polyester resin particles, the polybasic carboxylic acid preferably contains a dicarboxylic acid having a furan structure. The dicarboxylic acid having a furan structure more preferably contains a 2,5-furandicarboxylic acid unit, and even more preferably contains 2,5-dimethyl furandicarboxylate. The polyester resin according to one embodiment of the present invention may contain 50 to 100 mol %, and preferably 70 to 100 mol %, of structural units derived from dicarboxylic acids having a furan structure, relative to 100 mol % of structural units derived from polyvalent carboxylic acids contained in the polyester resin. The content of structural units derived from dicarboxylic acids having a furan structure is, for example, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, or 100 mol %, and may be within a range between any two of the numerical values ​​exemplified here.

[0018] In addition, when high biodegradability is required for the polyester resin particles, the polyvalent carboxylic acids may contain aliphatic dicarboxylic acids. The polyester resin according to one embodiment of the present invention may contain 0 to 50 mol% of constitutional units derived from aliphatic dicarboxylic acids relative to 100 mol% of constitutional units derived from polyvalent carboxylic acids contained in the polyester resin. The content of constitutional units derived from aliphatic dicarboxylic acids is, for example, 0, 5, 10, 15, 20, 25, 30, 35, 40, 45, or 50 mol%, and may be within a range between any two of the numerical values ​​exemplified here.

[0019] When a high refractive index is required for the polyester resin particles, the polyvalent carboxylic acids preferably contain aromatic dicarboxylic acids. When particularly high biodegradability is required for the polyester resin particles, the amount of aromatic dicarboxylic acids contained in the polyvalent carboxylic acids is preferably small. The polyester resin according to one embodiment of the present invention may contain 0 to 50 mol% of structural units derived from aromatic dicarboxylic acids relative to 100 mol% of structural units derived from polyvalent carboxylic acids contained in the polyester resin. The content of structural units derived from aromatic dicarboxylic acids is, for example, 0, 5, 10, 15, 20, 25, 30, 35, 40, 45, or 50 mol%, and may be within a range between any two of the numerical values ​​exemplified here.

[0020] <Polyhydric alcohol> Examples of polyhydric alcohols include aliphatic diols such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, 1,3-propanediol, 2,4-dimethyl-2-ethylhexane-1,3-diol, 2-methyl-1,3-propanediol, 2,2-dimethyl-1,3-propanediol (neopentyl glycol), 2-ethyl-2-butyl-1,3-propanediol, 2-ethyl-2-isobutyl-1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, and 2,2,4-trimethyl-1,6-hexanediol; Alicyclic diols such as 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, spiroglycol, tricyclodecane dimethanol, adamantanediol, and 2,2,4,4-tetramethyl-1,3-cyclobutanediol; Aromatic diols such as 4,4'-thiodiphenol, 4,4'-methylenediphenol, bisphenol S, bisphenol A, bisphenol fluorene, 4,4'-dihydroxybiphenyl, o-, m- and p-dihydroxybenzene, 2,5-naphthalenediol, and p-xylenediol; Ethylene oxide and propylene oxide adducts of these aromatic diols; Diols having a furan structure such as furan methanol and 2,3-furan diol; These may be used alone or in combination of two or more. The polyhydric alcohol may also include a hydrophilic group-containing polyhydric alcohol, as described below. The hydrophilic group-containing polyhydric alcohol will be described later.

[0021] The type of polyhydric alcohol used can be selected according to the properties required for the polyester resin particles. For example, when biodegradability and a high refractive index are required for the polyester resin particles, the polyhydric alcohol can include a diol having a furan structure. The diol having a furan structure preferably includes furan dimethanol. The polyester resin according to one embodiment of the present invention may contain 0 to 50 mol % of a structural unit derived from a diol having a furan structure relative to 100 mol % of a structural unit derived from a polyhydric alcohol contained in the polyester resin. The content of the structural unit derived from a diol having a furan structure is, for example, 0, 5, 10, 15, 20, 25, 30, 35, 40, 45, or 50 mol %, and may be within a range between any two of the numerical values ​​exemplified here.

[0022] In addition, when high biodegradability, sphericity and water resistance are required for the polyester resin particles, the polyhydric alcohol preferably contains an aliphatic diol. The aliphatic diol preferably contains an aliphatic diol having 2 to 4 carbon atoms, more preferably a straight-chain aliphatic diol having 2 to 4 carbon atoms, and more preferably a straight-chain aliphatic diol having 2 to 4 carbon atoms. The polyester resin according to one embodiment of the present invention may contain 50 to 100 mol % of aliphatic diol-derived structural units relative to 100 mol % of polyhydric alcohol-derived structural units contained in the polyester resin. The content of the aliphatic diol-derived structural units may be, for example, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, or 100 mol %, and may be within a range between any two of the numerical values ​​exemplified here.

[0023] When a particularly high refractive index is required for the polyester resin particles, the polyhydric alcohol preferably contains an aromatic diol. When a particularly high biodegradability is required for the polyester resin particles, the amount of aromatic diol contained in the polyhydric alcohol is preferably small. The polyester resin according to one embodiment of the present invention may contain 50 to 100 mol% of structural units derived from aromatic diols relative to 100 mol% of structural units derived from polyhydric alcohols contained in the polyester resin. The content of structural units derived from aliphatic diols is, for example, 0, 5, 10, 15, 20, 25, 30, 35, 40, 45, or 50 mol%, and may be within a range between any two of the numerical values ​​exemplified here.

[0024] <Hydrophilic Group-Containing Polyvalent Carboxylic Acids and Hydrophilic Group-Containing Polyhydric Alcohols> The polyester resin according to one embodiment of the present invention preferably has a hydrophilic group. If the polyester resin has a hydrophilic group, for example, when the polyester resin is dispersed in water, a dispersion liquid in which the polyester resin is finely dispersed in a solvent containing water can be obtained more stably. In addition, the polyester resin particles have amphiphilicity and act as a surfactant, so that not only can the polyester resin itself be dispersed in a solvent containing water, but also it is possible to emulsify a substance that has low dispersibility in a solvent containing water. Examples of the hydrophilic group include a sulfonic acid group, a sulfonate group, a carboxy group, an amino group, a phosphoric acid group, an ether group, etc. The hydrophilic group preferably contains a sulfonic acid group. The polyester resin according to one embodiment of the present invention may contain at least one of a structural unit derived from a hydrophilic group-containing polyvalent carboxylic acid and a structural unit derived from a hydrophilic group-containing polyhydric alcohol. The method of imparting hydrophilic groups to a polyester resin is not particularly limited, but the polyester resin can be imparted with hydrophilic groups by using a hydrophilic group-containing polyvalent carboxylic acid and / or a hydrophilic group-containing polyhydric alcohol as a monomer used in the synthesis of the polyester resin. Alternatively, a structure containing a hydrophilic group can be added after obtaining a polyester resin by polycondensing raw material monomers containing polyvalent carboxylic acids and polyhydric alcohols. As an example, a method of obtaining a polyester resin containing a carboxy group can be mentioned in which a polyester resin is obtained by polycondensing raw material monomers containing any polyvalent carboxylic acids and polyhydric alcohols, and then a tricarboxylic acid is added to obtain a polyester resin containing a carboxy group.

[0025] The hydrophilic group-containing polyvalent carboxylic acid preferably contains at least one of a sulfonic acid group-containing dicarboxylic acid and a sulfonate group-containing dicarboxylic acid, and more preferably contains a sulfonate group-containing dicarboxylic acid. Examples of the sulfonate group-containing dicarboxylic acid include sodium dimethyl 4-sulfoisophthalate, sodium dimethyl 5-sulfoisophthalate, sodium dimethyl 5-sulfoisophthalate, ammonium 5-sulfoisophthalate, potassium dimethyl 4-sulfoisophthalate, potassium dimethyl 5-sulfoisophthalate, sodium sodium 2-sulfoterephthalate, potassium dimethyl 2-sulfoterephthalate, potassium dimethyl 2-sulfoterephthalate, sodium diethylene glycol 2-sulfoterephthalate, and the like. Among these, it is preferable to contain sodium dimethyl 5-sulfoisophthalate.

[0026] The hydrophilic group-containing polyvalent carboxylic acids and the hydrophilic group-containing polyhydric alcohols can be used alone or in combination of two or more kinds.

[0027] The polyester resin according to one embodiment of the present invention has a constitutional unit derived from a polyvalent carboxylic acid and a constitutional unit derived from a polyhydric alcohol, and may have a constitutional unit derived from another monomer. Examples of the other monomer include monocarboxylic acid and monoalcohol, and trivalent or more polyvalent carboxylic acids such as tricarboxylic acids and trivalent or more polyhydric alcohols such as triols. The polyester resin according to one embodiment of the present invention preferably has a total of 90 mol% or more of constitutional units derived from polyvalent carboxylic acids and constitutional units derived from polyhydric alcohols, relative to a total of 100 mol% of constitutional units derived from polyvalent carboxylic acids contained in the polyester resin, constitutional units derived from polyhydric alcohols, and constitutional units derived from other monomers that may be contained as necessary. The total amount of constitutional units derived from polyvalent carboxylic acids and constitutional units derived from polyhydric alcohols is, for example, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, or 100 mol%, and may be within a range between any two of the numerical values ​​exemplified here.

[0028] As described above, the polyester resin according to one embodiment of the present invention may have a structural unit derived from a polyvalent carboxylic acid having three or more valences, such as a tricarboxylic acid, and a polyhydric alcohol having three or more valences, such as a triol. By having these structures, a crosslinked structure can be introduced into the obtained polyester resin. Examples of trivalent or higher carboxylic acids include trimellitic acid, pyromellitic acid, adamantanetricarboxylic acid, trimesic acid, and carboxylates thereof. Examples of trihydric or higher polyhydric alcohols include pentaerythritol, dipentaerythritol, tripentaerythritol, glycerin, trimethylolpropane, trimethylolethane, 1,3,6-hexanetriol, and adamantanetriol.

[0029] The polyester resin according to one embodiment of the present invention preferably contains a structural unit derived from a monomer having a furan structure and a structural unit derived from a monomer having a hydrophilic group.More preferably, the polyester resin according to one embodiment of the present invention contains a structural unit derived from a monomer having a furan structure, a structural unit derived from a monomer having a hydrophilic group, and a structural unit derived from an aliphatic diol.

[0030] <Content of each structural unit in polyester resin> The polyester resin according to one embodiment of the present invention preferably contains 25 to 60 mol% of structural units derived from monomers having a furan structure (including structural units derived from polycarboxylic acids having a furan structure and structural units derived from polyhydric alcohols having a furan structure) relative to the total of 100 mol% of structural units derived from polyvalent carboxylic acids and structural units derived from polyhydric alcohols (as well as structural units derived from other monomers that may be contained as necessary) contained in the polyester resin. The content of the structural units derived from monomers having a furan structure is, for example, 25, 30, 35, 40, 45, 50, 55, or 60 mol%, and may be within a range between any two of the numerical values ​​exemplified here. When the content of the structural unit derived from the monomer having a furan structure is within the above numerical range, it is easy to achieve both higher biodegradability and a high refractive index.

[0031] The polyester resin according to one embodiment of the present invention may contain 0.5 to 20 mol% of hydrophilic group-containing structural units (including structural units derived from polyvalent carboxylic acids having hydrophilic groups and structural units derived from polyhydric alcohols having hydrophilic groups) relative to the total of 100 mol% of structural units derived from polyvalent carboxylic acids and structural units derived from polyhydric alcohols having hydrophilic groups contained in the polyester resin (as well as structural units derived from other monomers that may be contained as necessary). The content of the hydrophilic group-containing structural units may be, for example, 0.5, 1, 2, 3, 4, 5, 10, 15, or 20 mol%, and may be within a range between any two of the numerical values ​​exemplified here. If the content of the hydrophilic group-containing structural units is within the above numerical range, for example, when dispersing polyester resin particles in water, a dispersion in which the polyester resin is finely dispersed more stably can be obtained. In addition, the polyester resin particles have amphiphilicity and act as a surfactant, and not only is the polyester resin itself dispersible in a solvent containing water, but it is also possible to emulsify a substance that has low dispersibility in a solvent containing water.

[0032] The polyester resin according to one embodiment of the present invention may contain 40 to 60 mol% of the structural units derived from polyvalent carboxylic acids relative to the total of 100 mol% of the structural units derived from polyvalent carboxylic acids and the structural units derived from polyhydric alcohols (and structural units derived from other monomers that may be contained as necessary) contained in the polyester resin. The content of the structural units derived from polyvalent carboxylic acids is, for example, 40, 45, 50, 55, or 60 mol%, and may be within a range between any two of the numerical values ​​exemplified here. In addition, when the polyester resin contains structural units derived from hydrophilic group-containing polyvalent carboxylic acids, the hydrophilic group-containing polyvalent carboxylic acids are included in the polyvalent carboxylic acids.

[0033] The polyester resin according to one embodiment of the present invention may contain 40 to 60 mol% of a structural unit derived from a polyhydric alcohol relative to a total of 100 mol% of the structural units derived from polyvalent carboxylic acids and the structural units derived from a polyhydric alcohol (as well as structural units derived from other monomers that may be contained as necessary) contained in the polyester resin. The content of the structural units derived from a polyhydric alcohol is, for example, 40, 45, 50, 55, or 60 mol%, and may be within a range between any two of the numerical values ​​exemplified here. In addition, when the polyester resin contains a structural unit derived from a hydrophilic group-containing polyhydric alcohol, the hydrophilic group-containing polyhydric alcohol is included in the polyhydric alcohol. The type and amount of structural units contained in the polyester resin can be determined by analysis using NMR or GC-MS, specifically, by the method described in the examples.

[0034] 1.2 Characteristics of polyester resin The polyester resin preferably has a glass transition temperature of 40° C. or higher. The glass transition temperature may be, for example, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 110, 120, 130, 140, or 150° C., and may be within a range between any two of the values ​​exemplified here. When the glass transition temperature is within the above numerical range, the heat resistance of the resulting particles is excellent. Although the glass transition temperature of a general biodegradable polymer is 40° C. or lower except for polylactic acid, the polyester resin of the present invention can achieve both biodegradability and heat resistance. The glass transition temperature can be measured by the method described in the examples. The glass transition temperature can be controlled by adjusting the type and composition ratio of the raw material monomers constituting the polyester resin, and the manufacturing conditions of the polyester resin.

[0035] The polyester resin preferably has a number average molecular weight of 3000 to 10000. The number average molecular weight may be, for example, 3000, 4000, 5000, 6000, 7000, 8000, 9000, or 10000, and may be within a range between any two of the numerical values ​​exemplified here. When the number average molecular weight is within the above numerical range, the particles obtained have sufficient water resistance. The number average molecular weight can be measured by the method described in the examples. In addition, the number average molecular weight can be controlled by adjusting the type and composition ratio of the raw material monomers constituting the polyester resin, and the manufacturing conditions of the polyester resin.

[0036] 1.3 Characteristics of polyester resin particles The average particle size of the polyester resin particles according to one embodiment of the present invention can be 1 to 30 μm. The average particle size of the polyester resin particles can be, for example, 1, 3, 5, 10, 15, 20, 25, or 30 μm, and may be within a range between any two of the numerical values ​​exemplified here. The average particle size of the polyester resin particles can be controlled by adjusting the polyester resin or the manufacturing conditions when granulating the polyester resin. The average particle size of the polyester resin particles can be D50 of the volume-based particle size by the laser diffraction method. The average particle size of the polyester resin particles can be measured, for example, by Mastersizer 3000 (manufactured by Malvern).

[0037] The sphericity of the polyester resin particles according to one embodiment of the present invention can be 0.85 or more, preferably 0.90 or more, and is, for example, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1.00, and may be within a range between any two of the numerical values ​​exemplified here. The sphericity of the polyester resin particles can be measured by the method described in the Examples. The sphericity of the polyester resin particles can be controlled by adjusting the polyester resin or the manufacturing conditions when the polyester resin is granulated. When the sphericity of the polyester resin particles is within the above range, the particles have excellent coefficient of friction and soft focus properties, which are required when the particles are used for cosmetics.

[0038] The refractive index of the polyester resin particles according to one embodiment of the present invention can be 1.50 or more, for example, 1.50, 1.55, 1.60, 1.65, 1.70, 1.75, 1.80, 1.85, 1.90, 1.95, 2.00, and may be within a range between any two of the numerical values ​​exemplified here. The refractive index of the polyester resin particles can be measured by the method described in the examples. The refractive index of the polyester resin particles can be controlled by the manufacturing conditions of the polyester resin (the type and composition ratio of the raw material monomers constituting the polyester resin).

[0039] The polyester resin particles according to one embodiment of the present invention preferably have crystallinity. The crystallinity is considered to be one of the factors that determine the water resistance of the polyester resin particles. Specifically, the polyester resin particles preferably have at least one melting point (Tm). Tm can be measured by the method described in the Examples. The crystallinity can be controlled by adjusting the production conditions of the polyester resin (types and composition ratios of raw material monomers constituting the polyester resin) and the production conditions of the polyester resin particles. In addition, the polyester resin particles according to one embodiment of the present invention preferably have a crystallinity of more than 5%. The crystallinity of the polyester resin particles according to one embodiment of the present invention is, for example, 6, 10, 15, 20, 25, 30, 35, or 40%, and may be within a range between any two of the numerical values ​​exemplified here. The crystallinity can be calculated by the following formula. (Heat of fusion at Tm in DSC measurement - Heat of recrystallization) ÷ (Heat of fusion of complete crystal of PET resin [140.1 mJ / mg]) × 100

[0040] The polyester resin particles according to one embodiment of the present invention preferably have a biodegradability of 10% or more. The biodegradability may be, for example, 10, 20, 30, 40, 50, 60, 70, 80, 90, or 100%, and may be within a range between any two of the values ​​exemplified here. The biodegradability can be measured by the method described in the Examples. The biodegradability can be controlled by adjusting the production conditions of the polyester resin (types and composition ratios of raw material monomers constituting the polyester resin) and the production conditions of the polyester resin particles.

[0041] The friction coefficient of the polyester resin particles according to one embodiment of the present invention is, for example, 0.40, 0.45, 0.50, 0.55, 0.60, 0.65, 0.70, or 0.75, and may be within a range between any two of the numerical values ​​exemplified here. The soft focus property of the polyester resin particles according to one embodiment of the present invention is, for example, 0.85, 0.90, 0.95, 1.00, 1.05, 1.10, 1.15, 1.20, 1.25, 1.30, 1.35, or 1.40, and may be within a range between any two of the numerical values ​​exemplified here. The oil absorption of the polyester resin particles according to one embodiment of the present invention is, for example, 80, 85, 90, 95, 100, 105, 110, 115, 120, 125, 130, 135, or 140 ml / 100 g, and may be within a range between any two of the numerical values ​​exemplified here. The friction coefficient, soft focus property, and oil absorption can be measured by the method described in the Examples. The friction coefficient, soft focus property, and oil absorption can be controlled by adjusting the production conditions of the polyester resin (types and composition ratios of raw material monomers constituting the polyester resin), etc. If the friction coefficient, soft focus property, and / or oil absorption are within the above numerical ranges, the composition can be more suitably used, for example, in cosmetics.

[0042] The polyester resin particles according to one embodiment of the present invention preferably have water resistance, and preferably have no change in particle shape and particle size after one week of immersing the obtained particles in water. The method for evaluating water resistance can be, for example, as described in the examples. Water resistance can be controlled by adjusting the crystallinity of the polyester resin particles, the hydrophilicity of the resin, and the conditions during the particle production process.

[0043] The polyester resin particles according to one embodiment of the present invention have high sphericity, high refractive index, high biodegradability, and / or high water resistance. Furthermore, by using the polyester resin particles in combination with a functionalizing agent such as a conductive polymer, it is possible to impart a desired function such as electrical conductivity. The polyester resin particles according to one embodiment of the present invention can be used for various applications such as matting agents, antiblocking agents, paint additives, carriers for chromatography, carriers for medicines, powder paints, gap adjusters, toners for electrophotography, electrorheological fluids, cosmetics, and conductive materials. Examples of the cosmetics include cosmetics in liquid, gel, and solid forms, such as foundations, face powders, eyeshadows, eyeliners, eyebrows, blushers, lipsticks, and nail colors.

[0044] 2. Manufacturing method of polyester resin particles The method for producing the polyester resin particles according to the present invention is not particularly limited. The polyester resin particles according to one embodiment of the present invention can be obtained by a production method including a spray drying step, in which an aqueous dispersion in which raw material fine particles containing a polyester resin described below are dispersed in water is spray dried to obtain the polyester resin particles.

[0045] 2.1 Aqueous dispersion The aqueous dispersion according to one embodiment of the present invention can be a dispersion in which raw material fine particles containing a polyester resin are dispersed in a solvent containing water. The solvent of the aqueous dispersion according to one embodiment of the present invention includes water. Examples of water include natural water, purified water, distilled water, ion-exchanged water, and pure water, and among these, ion-exchanged water is preferred. The solvent of the aqueous dispersion according to one embodiment of the present invention may further include an organic solvent. Examples of the organic solvent include aliphatic monohydric alcohols such as methanol, ethanol, and isopropyl alcohol, ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone, and aromatic compounds such as toluene and xylene. The aqueous dispersion according to one embodiment of the present invention may include, for example, 50, 60, 70, 80, 90, 95, 99, or 100% by mass of water relative to 100% by mass of the solvent (total of water and organic solvent) contained in the aqueous dispersion, and may be within a range between any two of the numerical values ​​exemplified here. The aqueous dispersion according to the present invention may not include an organic solvent.

[0046] 2.1.1 Raw material fine particles The raw material fine particles according to the present invention contain a polyester resin. The raw material microparticles according to one embodiment of the present invention preferably have polyester resin as a main component. As an example, the raw material microparticles according to one embodiment of the present invention may have a polyester resin content of, for example, 50, 60, 70, 80, 90, 95, 99, or 100% by mass relative to 100% by mass of raw material microparticles, and may be within a range between any two of the values ​​exemplified here. The raw material microparticles according to one embodiment of the present invention may be composed of only polyester resin. The types and amounts of the structural units contained in the polyester resin, the glass transition temperature, and the number average molecular weight are as described above with respect to the polyester resin contained in the polyester resin particles.

[0047] The average particle diameter of the raw material fine particles is preferably 10 to 400 nm. The average particle diameter of the raw material fine particles is, for example, 10, 20, 30, 40, 50, 100, 150, 200, 250, 300, 350, 400 nm, and may be within a range between any two of the numerical values ​​exemplified here. By forming a dispersion liquid in which the average particle diameter of the raw material fine particles is within the above numerical value range and the raw material fine particles are stably dispersed in a solvent containing water, a plurality of raw material fine particles (and other particles and components blended as necessary) can be stably attached in the spray drying process to obtain polyester resin particles.

[0048] The raw material microparticles having an average particle size within the above numerical range can be prepared, for example, by adjusting the manufacturing conditions of the raw material microparticles and the conditions when dispersing the polyester resin in a solvent. In order to obtain a dispersion in which the raw material microparticles are more stably dispersed in a solvent containing water, for example, the polyester resin can be provided with a hydrophilic group and / or an emulsifier or surfactant can be added to the dispersion. The average particle size of the raw material microparticles can be the D50 of the volume-based particle size measured by dynamic light scattering. The average particle size of the raw material microparticles in the aqueous dispersion can be measured, for example, by an ultrasensitive nanoparticle size distribution measuring device UPA-UT151 (manufactured by Microtrac).

[0049] The polyester resin in the raw microparticles preferably has no crystallinity or a crystallinity of 5% or less. The crystallinity of the polyester resin in the raw microparticles may be, for example, 0, 1, 2, 3, 4, or 5%, and may be within a range between any two of the values ​​exemplified here. The crystallinity is determined by the same method as above. By having no crystallinity or by having a crystallinity lower than the upper limit, the sphericity of the polyester resin particles obtained by spray drying can be further improved. The crystallinity can be controlled by adjusting the types and composition ratios of the raw material monomers constituting the polyester resin and the production conditions of the polyester resin. The crystallinity of the polyester resin in the raw material fine particles is preferably 0 to 5%, and the crystallinity of the polyester resin particles and the polyester resin in the polyester resin particles is preferably more than 5%.

[0050] <Method of producing polyester resin> The method for producing the polyester resin according to the present invention is not particularly limited. The method for producing the polyester resin according to one embodiment of the present invention includes a step of polycondensing raw material monomers including at least a polyvalent carboxylic acid and a polyhydric alcohol to obtain a polyester resin. The raw material monomers include at least polyvalent carboxylic acids and polyhydric alcohols, and may also include other monomers. The polyvalent carboxylic acids, polyhydric alcohols, and other monomers may each be the monomers described above. The amount of each raw material monomer is preferably adjusted so that the amount of each structural unit in the resulting polyester resin is within the above-mentioned numerical range. As an example, the polyhydric alcohol can be added in an excess amount relative to the polyvalent carboxylic acids. Since almost the entire amount of the polyvalent carboxylic acids reacts, the amount of each structural unit in the resulting polyester resin can also be roughly calculated from the amount of the polyvalent carboxylic acids.

[0051] In the polycondensation step, an esterification reaction is first carried out, and then a polycondensation reaction is carried out.

[0052] In the esterification reaction, a catalyst can be used, and specific examples thereof include titanium-based catalysts such as tetraisopropyl titanate (titanium tetraisopropoxide), tetrabutyl titanate, etc., antimony-based catalysts such as antimony trioxide, germanium-based catalysts such as germanium dioxide, etc., and catalysts such as zinc acetate, manganese acetate, dibutyltin oxide, etc. As an example, it is preferable to use titanium tetraisopropoxide.

[0053] The amount of the catalyst to be added can be 0.0001 to 0.1 mol, and preferably 0.0005 to 0.01 mol, per 100 mol of the raw material monomer. The reaction temperature during the esterification reaction can be 150 to 210° C., for example, 150, 160, 170, 180, 190, 200, or 210° C., and may be within a range between any two of the values ​​exemplified here. By setting the amount of catalyst and the reaction temperature within the above numerical ranges, the reaction proceeds sufficiently and side reactions tend not to occur easily. The reaction can be carried out in an atmosphere of an inert gas such as nitrogen, and can be carried out at normal pressure.

[0054] After the esterification reaction has been carried out, a polycondensation reaction can be carried out. The polycondensation reaction can be carried out immediately after the esterification reaction without adding any new catalyst, or the same catalyst as that used in the above esterification reaction can be further added in the same amount. The reaction temperature during the polycondensation reaction can be 200 to 260° C., for example, 200, 210, 220, 230, 240, 250, or 260° C., and may be within a range between any two of the numerical values ​​exemplified here. The reaction can be carried out under reduced pressure, for example, 500, 1000, 1500, 2000, 2500, or 3000 Pa, and may be within a range between any two of the numerical values ​​exemplified here.

[0055] <Concentration of polyester resin in aqueous dispersion> The concentration of the polyester resin (raw material fine particles) in the aqueous dispersion according to one embodiment of the present invention can be 0.01 to 35% by mass. The concentration of the polyester resin is, for example, 0.01, 0.03, 0.05, 0.1, 0.5, 1, 5, 0, 5, 10, 15, 20, 25, 30, or 35% by mass, and may be within a range between any two of the numerical values ​​exemplified here.

[0056] 2.1.2 Other ingredients The aqueous dispersion according to the present invention contains at least the raw material fine particles and water, and may contain other components as necessary.

[0057] The aqueous dispersion according to one embodiment of the present invention may contain an emulsifier or a dispersant. By using an emulsifier or a dispersant, it may be possible to obtain a dispersion in which the raw material fine particles are more stably dispersed in a solvent containing water. As the emulsifier and dispersant, a nonionic surfactant, an anionic surfactant, a cationic surfactant, etc. can be used.

[0058] Examples of nonionic surfactants include polyoxyethylene alkyl ethers such as polyoxyethylene lauryl ether and polyoxyethylene stearyl ether; polyoxyalkylene derivatives such as polyoxyethylene alkylene alkyl ether; polyoxyalkylene alkenyl ether and polyoxyethylene alkylphenyl ether; sorbitan fatty acid esters such as sorbitan monolaurate and sorbitan monostearate; polyoxyethylene sorbitan fatty acid esters such as polyoxyethylene sorbitan monolaurate and polyoxyethylene sorbitan monooleate; polyoxyethylene sorbitol fatty acid esters and glycerin fatty acid esters; polyoxyethylene fatty acid esters such as polyethylene glycol monolaurate and polyethylene glycol distearate; polyoxyethylene hydrogenated castor oil, polyoxyethylene alkylamines, and alkyl alkanolamides. Examples of the anionic surfactant include alkyl sulfate salts such as sodium lauryl sulfate and ammonium lauryl sulfate; polyoxyethylene alkyl sulfate salts, sodium dodecylbenzenesulfonate, sodium dialkylsulfosuccinate, polyoxyalkylene alkenyl ether ammonium sulfate, fatty acid salts, and sodium salts of naphthalenesulfonic acid-formaldehyde condensates. Examples of cationic surfactants include alkylamine salts such as coconut amine acetate and stearyl amine acetate; quaternary ammonium salts such as lauryl trimethyl ammonium chloride, stearyl trimethyl ammonium chloride, cetyl trimethyl ammonium chloride and alkyl benzyl dimethyl ammonium chloride; and examples of amphoteric surfactants include alkyl betaines such as stearyl betaine, lauryl betaine and lauryl dimethyl amine oxide, and alkyl amine oxides. These can be used alone or in combination of two or more.

[0059] From the viewpoint of environmental consideration, simplification of the manufacturing process, and cost reduction, the concentration of the emulsifier and dispersant in the aqueous dispersion according to one embodiment of the present invention can be 5% by mass or less. The concentration of the emulsifier and dispersant can be, for example, 0, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, or 5.0% by mass, and may be within a range between any two of the numerical values ​​exemplified here. The aqueous dispersion according to one embodiment of the present invention may not contain an emulsifier or dispersant. In this case, a dispersion in which the raw material fine particles are stably dispersed in a solvent containing water can be formed by another means, such as imparting a hydrophilic group to the polyester resin.

[0060] In order to impart desired functions to the polyester resin particles finally obtained, a functionalizing agent may be added to the aqueous dispersion according to one embodiment of the present invention. Examples of the functionalizing agent include a conductive polymer, an inorganic fine particle emulsion, a water-soluble substance, and an oil-soluble substance. The conductive polymer may be a π-conjugated conductive polymer such as polythiophene. Examples of inorganic fine particle emulsions include nanoparticle emulsions of zirconium, aluminum, titanium, etc.; examples of water-soluble substances include water-soluble pigments, fragrances, medicines, pesticides, etc.; and examples of oil-soluble substances include oil-soluble pigments, fragrances, medicines, pesticides, etc.

[0061] The aqueous dispersion according to one embodiment of the present invention may contain 0 to 50 parts by mass of a functionality imparting agent relative to 100 parts by mass of polyester resin. The content of the functionality imparting agent relative to 100 parts by mass of polyester resin may be, for example, 0, 5, 10, 15, 20, 25, 30, 35, 40, 45, or 50 parts by mass, and may be within a range between any two of the numerical values ​​exemplified here.

[0062] 2.1.3 Characteristics of aqueous dispersion The viscosity of the aqueous dispersion is preferably 50 mPa·s or less. The viscosity may be, for example, 0.5, 1, 5, 10, 20, or 50 mPa·s, and may be within a range between any two of the values ​​exemplified here. By adjusting the viscosity in this range, polyester resin particles having an appropriate shape and / or structure can be obtained. The viscosity of the aqueous dispersion can be measured using a tuning fork vibro viscometer SV-1A (manufactured by A&D).

[0063] 2.1.4 Aqueous dispersion preparation process The method for preparing the aqueous dispersion is not particularly limited, but the aqueous dispersion can be prepared by adding the polyester resin (fine particles) to a solvent containing water and stirring with a known stirrer. For example, a disperser mixer, a homomixer, a high-pressure homogenizer, etc. can be used. In the dispersion preparation step according to one embodiment of the present invention, the polyester resin and other components to be blended as necessary can be added to a solvent containing water, and heated and stirred. The heating temperature can be 20 to 100° C., for example, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, or 100° C., and may be within a range between any two of the numerical values ​​exemplified here. The stirring time can be 10 to 300 minutes, for example, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 200, or 300 minutes, and may be within a range between any two of the numerical values ​​exemplified here. In the dispersion preparation step, a treatment for adjusting the viscosity or rheological properties of the dispersion may be carried out as necessary. For example, a treatment for lowering the viscosity, particularly the dynamic viscosity at high shear, or a treatment for imparting pseudoplasticity or thixotropy can be mentioned. For example, these treatments can be carried out by adding a dispersant or by reducing the molecular weight of the organic material.

[0064] 2.2 Spray drying process In the spray drying process, the aqueous dispersion in which the raw material fine particles containing the polyester resin are dispersed in water is spray-dried to obtain polyester resin particles. In the spray drying process, the raw material fine particles and other particles or components that are mixed as necessary are adhered to each other, thereby obtaining polyester resin particles.

[0065] In the spray drying step, the aqueous dispersion is supplied to a spray dryer adjusted to a predetermined temperature, and sprayed to obtain polyester resin particles. The spray dryer is not particularly limited as long as it is a spray dryer used in the production of ordinary granules. The spray dryer is - Raw material tank for storing aqueous dispersions, A raw material supply pump for supplying the aqueous dispersion liquid; Nozzles (four-fluid nozzles, two-fluid nozzles, or one-fluid nozzles) or rotating disks that turn aqueous dispersions into fine droplets, A drying chamber for drying and granulating the droplets; Blowers, filters, heaters for blowing dried and heated air or inert gas into the drying chamber, and A collector that collects the composite powder precursor using a two-point collection method, a cyclone method, a bag filter method, etc. (These may be heatable collectors.) etc. may be provided.

[0066] The spray dryer may be equipped with a nozzle that turns the aqueous dispersion into fine droplets, such as a four-fluid nozzle, a two-fluid nozzle, or a one-fluid nozzle, or a rotating disk. When the spray dryer has a nozzle that turns the aqueous dispersion into fine droplets, the air pressure may be, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, or 1 MPa, or may be within a range between any two of the numerical values ​​exemplified here. When the spray dryer has a rotating disk, the disk rotation speed may be, for example, 10,000, 20,000, 30,000, 40,000, or 50,000 rpm, or may be within a range between any two of the numerical values ​​exemplified here.

[0067] The liquid delivery rate may be, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, or 1 L / hr, or may be within a range between any two of the numerical values ​​exemplified here. The spray drying step is preferably carried out at a temperature 25° C. or more higher than the glass transition temperature of the polyester resin. The difference between the temperature at which the spray drying step is carried out and the glass transition temperature of the polyester resin can be, for example, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 105, 110, 115, 120, 125, 130, 135, 140, 145, 150, 155, 160, 165, 170, 175, 180, 185, 190, 195, 200, 205, or 210° C., or may be within a range between any two of the values ​​exemplified here. The temperature at the inlet where the aqueous dispersion is introduced into the apparatus (inlet temperature) can be 65 to 250° C. The inlet temperature is, for example, 65, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, or 250° C., and may be within a range between any two of the numerical values ​​exemplified here. By adjusting the droplet formation conditions and drying conditions in the spray drying step, the shape, structure and physical properties of the resulting polyester resin particles can be adjusted.

[0068] In the spray drying process according to one embodiment of the present invention, a plurality of raw material fine particles and other particles or components that are blended as necessary are stuck together to obtain polyester resin particles. The average particle diameters of the raw material fine particles and the polyester resin particles are as described above.

[0069] The average particle size of the polyester resin particles according to one embodiment of the present invention can be larger than the average particle size of the raw material fine particles. The average particle size of the polyester resin particles according to one embodiment of the present invention is preferably 10 times or more larger than the average particle size of the raw material fine particles. The average particle size of the polyester resin particles may be, for example, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 200, 300, 400, or 500 times the average particle size of the raw material fine particles, and may be within a range between any two of the numerical values ​​exemplified here. In addition, the polyester resin particles are usually 1 μm or more, and the average particle size of the raw material fine particles is less than 1 μm. The two have different average particle sizes, and in order to calculate the average particle size more accurately, the average particle size can be calculated by different evaluation methods. Specifically, the average particle size of the polyester resin particles can be calculated using the D50 of the volume-based particle size by the laser diffraction method, and the average particle size of the raw material fine particles can be calculated using the D50 of the volume-based particle size by the dynamic light scattering method. EXAMPLES

[0070] The present invention will be described in more detail below based on examples, but the present invention is not limited to these examples.

[0071] Example 1 <Production of polyester resin> A flask equipped with a heating device, a thermometer, a stirrer, a rectification column, a nitrogen inlet tube, and a vacuum device was charged with 0.95 mmol of 2,5-dimethyl furandicarboxylate (FDCA-M), 0.05 mmol of sodium dimethyl 5-sulfoisophthalate (SIPM), 2 mmol of ethylene glycol (EG), and 0.000035 mmol of Orgatics TA-8 (titanium tetraisopropoxide: Matsumoto Fine Chemical Co., Ltd.) as a polymerization catalyst. The temperature in the flask was gradually raised to 180°C while introducing nitrogen, and the esterification reaction was carried out for 3 hours. Thereafter, the temperature in the flask was raised to 230°C, and the pressure was reduced to 2000 Pa, and a polycondensation reaction was carried out for 3 hours to produce a polyester resin. The polyester resin had an Mn of 7,000 and a glass transition temperature of 75.3°C.

[0072] <Production of aqueous dispersion containing raw material fine particles containing polyester resin> The polyester resin obtained above and ion-exchanged water were charged into a flask so that the polyester resin concentration was 20% by mass, and then the mixture was stirred at 80° C. for 1 hour to obtain an aqueous dispersion containing raw material fine particles. In the aqueous dispersion, the polyester resin was present as raw material fine particles having an average particle diameter of 284 nm. The average particle diameter of the raw material fine particles in the aqueous dispersion was determined as D50 of the volume-based particle diameter by dynamic light scattering. The average particle diameter of the raw material fine particles in the aqueous dispersion was measured by an ultra-high sensitivity nano particle size distribution measuring device UPA-UT151 (manufactured by Microtrac). The crystallinity of the raw material fine particles was 4.87%.

[0073] <Production of Polyester Resin Particles> The above aqueous dispersion was spray-dried under the following conditions using a spray dryer (Mini Spray Dryer B-290, manufactured by Nippon Buchi) to obtain polyester resin particles. The average particle diameter of the polyester resin particles was 6.7 μm. The average particle diameter of the polyester resin particles was taken as D50, the volume-based particle diameter measured by the laser diffraction method. The average particle diameter of the polyester resin particles was measured using a Mastersizer 3000 (manufactured by Malvern). Supply rate of aqueous dispersion: 0.6L / hr Air pressure: 0.2MPa Inlet temperature (temperature at the inlet where the aqueous dispersion is introduced into the device): 100°C Outlet temperature (the temperature at the outlet where the aqueous dispersion is spray-dried and discharged as particles): 35°C Dwell time: 2 seconds Nozzle: Two-fluid nozzle

[0074] The shape of the polyester resin particles was also observed using an electron microscope. The image is shown in Figure 1. The degree of crystallinity of the polyester resin particles was 11.05%.

[0075] (Examples 2 to 6, Comparative Example 1) Polyester resins according to Examples 2 to 6 and Comparative Example 1 were prepared in the same manner as in Example 1, except that the amounts of raw material monomers added were as shown in Table 1. In addition to the monomers used in Example 1, isophthalic acid (IPA) was used in Example 4 and Comparative Example 1, and diethylene glycol (DEG) was used in Example 5. In addition, the obtained polyester resin was used to obtain an aqueous dispersion containing raw material fine particles in the same manner as in Example 1. In the aqueous dispersion, the polyester resin was present as raw material fine particles having the average particle diameters shown in Table 1. Using the obtained aqueous dispersion, polyester resin particles were obtained in the same manner as in Example, except that the spray drying conditions were as shown in Table 1.

[0076] The polyester resin and polyester resin particles obtained by the following methods were evaluated.

[0077] (Polyester Resin Composition) The composition ratio of the polyester resin was determined by a nuclear magnetic resonance (NMR) method under the following conditions. Measuring device: ECZL-500G (manufactured by JEOL) Measurement method: 1 H-NMR Number of times: 16 Sample concentration: 10mg / ml Dilution solvent: DMSO-d6

[0078] (Glass transition temperature (Tg) of polyester resin) The polyester resin was placed in a simple sealed pan and measured using a differential scanning calorimeter (DSC). The temperature was raised from -80°C to 300°C at 10°C / min under a nitrogen stream, and the thermal change was measured to draw a DSC curve of "amount of heat absorbed and released" versus "temperature." The characteristic inflection point observed at this time was taken as Tg. The value obtained from the DSC curve by the midpoint method was used as Tg.

[0079] (Number average molecular weight (Mn) of polyester resin) The number average molecular weight (Mn) of the polyester resin was determined by gel permeation chromatography (GPC) under the following conditions. Measuring device: HLC-8320GPC (Tosoh) GPC column configuration: The following four columns (all manufactured by Tosoh) (1) TSKgel HxL-H (guard column) (2) TSKgel GMHxL (3) TSKgel GMHxL (4) TSKgel G2500HxL ·Flow rate: 1.0mL / min Column temperature: 40℃ Sample concentration: 1.5% (w / v) (diluted with tetrahydrofuran) Mobile phase solvent: Tetrahydrofuran Standard polystyrene equivalent

[0080] (Crystallization degree of raw material fine particles and polyester resin particles) The sample was sealed in a simple sealed pan and measured using a differential scanning calorimeter (DSC). The temperature was raised from -80°C to 300°C at 10°C / min under a nitrogen stream, and the heat change was measured, and a DSC curve of "endothermic heat amount" and "temperature" was drawn. From the DSC curve, the heat of fusion at Tm and the heat of recrystallization were calculated, and the degree of crystallinity was calculated using the following formula. (Heat of fusion at Tm in DSC measurement - Heat of recrystallization) ÷ (Heat of fusion of complete crystal of PET resin [140.1 mJ / mg]) × 100 The crystallinity of the raw material fine particles was measured after freeze-drying the aqueous dispersion in which the raw material fine particles were dispersed and distilling off the solvent.

[0081] (Average particle size of polyester resin particles) The average particle size of the polyester resin particles was determined as D50 of the volume-based particle size measured by a laser diffraction method using a Mastersizer 3000 (manufactured by Malvern Instruments).

[0082] (Sphericity of polyester resin particles) The measurement was carried out using a flow type particle image analyzer (FPIA-3000S, manufactured by Sysmex) according to the following method. A surfactant aqueous solution was obtained by adding 0.05 g of alkylbenzene sulfonate as a dispersant to 50 mL of ion-exchanged water. Then, 0.15 g of resin particles to be measured was added to the surfactant aqueous solution, and ultrasonic waves were irradiated for 5 minutes using an ultrasonic disperser to disperse the obtained particles in the surfactant aqueous solution, thereby obtaining a dispersion for measurement. For the measurement, the above-mentioned flow type particle image analyzer equipped with a standard objective lens (10x) was used, and Particle Sheath (PSE-900A: manufactured by Sysmex) was used as the sheath liquid used in the above-mentioned flow type particle image analyzer. The measurement dispersion liquid prepared according to the above procedure was introduced into the above-mentioned flow type particle image analyzer, and measurement was performed under the following measurement conditions. Measurement mode: HPF measurement mode Particle size measurement range: 0.500μm~200.0μm Measurement range of particle sphericity: 0.2 to 1.0 Number of particles measured: 30,000 The sphericity is a value obtained by dividing the perimeter calculated from the diameter of a perfect circle having the same projected area as the image of the resin particle by the perimeter of the image of the resin particle.

[0083] (Refractive index of polyester resin particles) One drop of each refractive index liquid of REFRACTIVE INDEX LIQUIDS manufactured by Cargille Laboratories was dropped onto the particle samples obtained in the examples and comparative examples, and the particles were observed under a microscope VHX-5000 (manufactured by KEYENCE). The refractive index of the refractive index liquid at which the boundary between the solid and liquid became invisible was regarded as the refractive index of the particles.

[0084] (Tm of polyester resin particles) The obtained polyester resin particles were sealed in a simple sealed pan and measured using a differential scanning calorimeter (DSC). The measurement was performed under a nitrogen gas flow, with the temperature rising from -80°C to 300°C at 10°C / min to measure the heat change, and a DSC curve of "endothermic heat amount" and "temperature" was drawn, and the peak top of the endothermic peak observed at this time was taken as Tm. The detection of the peak top (Tm) is an indicator that the polyester resin particles have crystallinity.

[0085] (Biodegradability of polyester resin particles (marine degradability)) 30 mg of polyester resin particles obtained in the Examples and Comparative Examples and 250 ml of seawater were placed in a brown sample bottle, and after the measurement head was set, the bottle was left to stand in a thermostatic chamber at 20°C for a predetermined period of time, and the BOD value was calculated. The biodegradability (%) was calculated using the following formula. The measurement head used was Oxi-Topi (manufactured by WTW). Biodegradability (%) = [(sample BOD value (mg) - blank BOD value (mg)) / theoretical oxygen demand of sample (mg)] x 100

[0086] (Water resistance of polyester resin particles) The obtained particles were immersed in water, and after one week, the particle size and particle diameter were measured using an SEM and a Mastersizer 3000 (manufactured by Malvern Instruments), and evaluated according to the following criteria. 〇: No change in shape or particle size △: No particle collapse was observed, but cracks and particle loss were observed. ×: Particles disintegrated

[0087] (Friction coefficient of polyester resin particles) 0.5 g of the obtained polyester resin particles was applied onto Bioskin (manufactured by Viewlux), and the friction coefficient was measured using a friction tester KES-SE (manufactured by Kato Tech) under the test conditions of a load of 50 g, a speed of 1 mm / sec, and a silicone contact. Under the above conditions, the friction coefficient was measured by scanning 30 mm, and the average value of the central 20 mm was taken as the friction coefficient.

[0088] (Soft focus properties of polyester resin particles) 0.5 g of the obtained polyester resin particles was applied onto Bioskin (manufactured by Viewlux), and measurements were performed using a goniophotometer GC-5000L (manufactured by Nippon Denshoku Industries Co., Ltd.), and the value [reflection intensity at 0° / reflection intensity at 45°] was calculated as a value indicating the soft focus property. Note that a halogen was used as the light source, and the incident angle was 45°.

[0089] (Oil absorption of polyester resin particles) 0.5 g of the obtained polyester resin particles was placed on a glass plate, linseed oil (Fujifilm Wako Pure Chemical Industries, first-class) was dropped, and the resin particles were kneaded until they became a hard putty (paste). The above operation was repeated, and the end point was the point at which the paste suddenly softened and began to flow when the glass plate was placed vertically. The oil absorption was calculated using the following formula. Oil absorption [mg / 100g] = (amount of linseed oil consumed [ml] / mass of polyester resin particles [g]) x 100

[0090] [Table 1]

[0091] The raw materials used in each of the examples and comparative examples are as follows. FDCA-M: Dimethyl furandicarboxylate SIPM: Sodium dimethyl 5-sulfoisophthalate IPA: Isophthalic acid EG: Ethylene glycol DEG: Diethylene glycol

Claims

1. Polyester resin particles comprising a polyester resin containing a furan structure.

2. The polyester resin particles according to claim 1 , wherein the polyester resin has a hydrophilic group.

3. The polyester resin contains a structure derived from a polyvalent carboxylic acid and a structure derived from a polyhydric alcohol, The polyester resin particles according to claim 1 or 2, wherein the structure derived from the polyvalent carboxylic acid contains the furan structure.

4. 4. The polyester resin particles according to claim 3, wherein the structure derived from the polyhydric alcohol includes a structure derived from a linear aliphatic diol having 2 to 4 carbon atoms.

5. 3. The polyester resin particles according to claim 1, having a sphericity of 0.90 to 1.

00.

6. 3. The polyester resin particles according to claim 1, having an average particle size of 1 to 30 μm.

7. A cosmetic comprising the polyester resin particles according to claim 1 or 2.

Citation Information

Patent Citations

  • Production of polyeter particle

    JP1994145367A

  • Polyester particle

    JP1994263882A